After Interpretation: Remembering Archaeology - Olsen, Bjørnar (Current Swedish Archaeology, 2012)
In the light of some significant anniversaries, this pa- per discusses the fate of archaeological theory after the heyday of postprocessualism. While once considered a radical and revolutionary alternative, post- processual or interpretative archaeology remarkably soon became normalized, mainstream and hegem- onic, leading to the theoretical lull that has charac- terized its aftermath. Recently, however, this consen- sual pause has been disrupted by new materialist per- spectives that radically depart from the postproces- sual orthodoxy. Some outcomes of these perspectives are proposed and discussed, the most significant be- ing a return to archaeology – an archaeology that sacrifices the imperatives of historical narratives, so- ciologies, and hermeneutics in favour of a trust in the soiled and ruined things themselves and the memo- ries they afford.